Cyanidin‐3‐Ο‐glucoside supplementation in cryopreservation medium improves human sperm quality. (7th June 2022) - Wang, Xiaohan; Li, Xusheng; Liu, Yixun; Jiang, Xiaohua; Wu, Limin; Liu, Ran; Jin, Rentao; Zhou, Naru; Cao, Cheng; Hu, Xuechun; Xu, Bo; Tong, Xianhong; et al.
Abstract: Currently, the cryopreservation of human spermatozoa must overcome the adverse effects of excessive oxidation. In this study, we aimed to evaluate the effect of supplementation of cryopreservation medium with cyanidin‐3‐ Ο ‐glucoside (C3G) on sperm quality. Semen samples were obtained from men with normozoospermia according to WHO criteria ( n  = 39). The sperm parameter values were compared after cryopreservation in medium supplemented with and without C3G.Compared with the control group (without additive), low doses (50 μM and 100 μM) of C3G improved sperm viability and motility and decreased the reactive oxygen species (ROS) of spermatozoa, while high doses (200 μM) of C3G did not obviously enhance sperm quality. The amount of DNA fragmentation index (DFI) and high DNA stainability (HDS) after freezing were higher in the control group than in the C3G supplementation groups. Low‐concentration C3G supplementation (50 μM) was negatively correlated with sperm ROS levels ( r  = −0.2, p  = 0.03). Collectively, our findings suggest that C3G could be an efficient semen cryoprotectant that ameliorates oxidative stress in human sperm during cryopreservation.